CPC-105 Pharmacoeconomic Aspects of the Treatment of Rheumatoid Arthritis with Tumour Necrosis Factor Alpha Antagonists: A Societal Perspective. (12th March 2013) - Marongiu, C; Francisco, C; Modena, V; Azzolini, V; Milla, P; Cattel, L
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disorder, affecting 1% of the population, characterised by pain, joint swelling and progressive destruction of joint tissue. EULAR (European League Against Rheumatism) recommends the use of Tumour Necrosis Factor alpha antagonists (anti-TNFα) if methotrexate or Disease Modifying Antirheumatic Drugs fail. Anti-TNFα treatment imposes a significant financial burden on hospital budgets. Purpose: To perform a pharmacoeconomic investigation in the Piedmont region (Italy) to identify the cost of the illness RA. To analyse the payer's and societal perspectives, investigating direct costs associated with health care use and indirect costs related to productivity loss. Materials and Methods: A multidisciplinary group, rheumatologists, hospital pharmacists and pharmacoeconomists, was established to perform a pharmacoeconomic evaluation of the direct and indirect costs of RA, by a systematic literature review. Afterward, we plan a perspective, observational, multicentre, cost-effectiveness analysis of RA biological drugs, involving 100 patients. Each patient will be recorded, every three months for one year, through personal data, disease duration and characterization, systemic manifestations and comorbidities, prescribed biological medicines. A questionnaire will be submitted, in order to assess direct and indirect costs. Results: 40 existing pharmacoeconomic evaluations were critically appraised: the overall mean costs of RA amounted to about €15, 000 per year, while the direct annual costs of RA were on average about €4, 000. The greatest burden of RA costs was the indirect costs. From a societal perspective the superior clinical outcomes achieved with anti-TNFα are worth their higher costs. The most favourable incremental cost-effectiveness ratio was for etanercept compared to methotrexate. Conclusions: The cost-effectiveness of an intervention depends on the maximum the decision makers are willing to pay for an extra unit of health effect. It should be considered that treatments with anti-TNFα, in a societal perspective, decrease the use of health resources and increase productivity. No conflict of interest.